2021
DOI: 10.1371/journal.pone.0257715
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of the relationship between coliform bacteria and water geochemistry in surface and ground water systems

Abstract: The occurrence of pollution indicator bacteria (total and faecal coliform) has been used as a sanitary parameter for evaluating the quality of drinking water. It is known that these indicators are associated with disease causing organisms which are of great concern to public health. This study assessed the relationship between coliform bacteria and water geochemistry in surface and ground water systems in the Tarkwa mining area using logistic regression models. In surface water sources, higher values of chlori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 36 publications
2
11
1
Order By: Relevance
“…When biological factors were accounted for in the surface water model, both faecal and total coliforms showed significant association with pH. Interestingly, total coliforms were associated with optimal pH values while faecal coliform were associated with non-optimal water pH, a similar observation was reported by Aram et al [ 39 ]. This further implied that total coliform bacteria survival is much favored in optimal pH conditions.…”
Section: Discussionsupporting
confidence: 80%
“…When biological factors were accounted for in the surface water model, both faecal and total coliforms showed significant association with pH. Interestingly, total coliforms were associated with optimal pH values while faecal coliform were associated with non-optimal water pH, a similar observation was reported by Aram et al [ 39 ]. This further implied that total coliform bacteria survival is much favored in optimal pH conditions.…”
Section: Discussionsupporting
confidence: 80%
“…The most prevalent anion (nucleophile) in the surface water, groundwater, and soil water is HCO 3 − and its typical concentration ranges between 100 and 1000 mg L −1 (0.0016–0.016 M). The other major anions, SO 4 2− , NO 3 − , Cl − , H 2 PO 4 − /HPO 4 2− , are present at the concentrations below 0.005 M, 39–42 which are lower than those analyzed in Table 3. Also, SO 4 2− and NO 3 − exhibit very low basicity as they derive from relatively strong acids.…”
Section: Discussionmentioning
confidence: 64%
“…Therefore, it can be anticipated that the general catalysis from anions in natural fresh waters will have negligible contribution into the DEB hydrolysis. In addition, the pH of surface water, groundwater, and soil water (pH 4–9) falls into the region of the neutral DEB hydrolysis (Figure 2), making the pH and temperature the crucial factors governing the compound stability 39,41–44 . The results of our prediction shown in Table 4 reveal that depending on the temperature of fresh waters that are met in the environment, the half‐life of DEB ranges from 2 days at 30°C to 31 days at 0°C.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Analysis of total Coliform bacteria in Pucang River water showed that the most extensive total coliform in 2018 was POS 2 of 281 MPN/100 ml, in 2019 from POS 1–7 the results were the same at 0.014 MPN/100 ml, in 2020, the largest was POS 5 and 7 of 920 MPN/100 ml (Exhibit 14). The group of coliform bacteria is one indicator of domestic waste contaminants in the waters (Aram et al., 2021). Coliform bacteria can transmit several diseases through water, especially stomach diseases such as typhoid, cholera, and dysentery.…”
Section: Resultsmentioning
confidence: 99%